Penentuan Persamaan Empiris Antara Debit Injeksi Air Dengan Produksi Minyak Bumi Di Eor Plant Balam - Utami, Syelvia Putri; Furqan, Muhammad; Chairul, Chairul (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
Along with the decreasing availability of oil in the layers of the earth, it is necessary support from the technology or new effort to increase oil production. One of them is by way of water injection where the produced water is injected back into the earth to push oil to the surface. This research studied the relationship between the discharge of water injection and time of water injection against discharge of oil production. Processing of the data in this study performed using Microsoft Excel and Minitab software. This research was conducted in two stages. The first stage is the collection of field data which includes data discharge of water injection and discharge of oil production. For the second phase of data analysis using regression and correlation. The results showed that the best results of equations to predict the flow of water injection relationship with discharge of oil production is an empirical equation Y = -137 774 + 0,783 X with R2 value 0,987. While the influence of injection water flow to the discharge of the most significant of oil production is 6 days after water was injected.Keyword : Discharge of Water Injection, Discharge of Oil Production, Water Injection Time, Minitab, Regression and Correlation